The Immunity Protection of Central Nervous System Induced by Pseudorabies Virus DelgI/gE/TK in Mice - Xu, Lei; Wei, Jian-feng; Zhao, Jun; Xu, Si-yao; Lee, Feng-qin; Nie, Min-cai; Xu, Zhi-wen; Zhou, Yuan-cheng; Zhu, Ling (Frontiers in Microbiology, 2022)
Based on a variant strain, we construct a gE/gI/TK-deleted PRV. 18 female mice were randomized to receive PRV XJ delgE/gI/TK (vaccination group), DMEM (vehicle group), and mock group to confirm the protection of PRV delgE/gI/TK on the central nervous system in mice. Subsequently, vaccination and vehicle group infected with PRV XJ. Mice in the vehicle group showed severe neurological symptoms and higher viral loads than the vaccination group. The exudation of Evans blue and the expression of tight junction protein showed no difference in all groups. HE staining showed vacuolar neuronal degeneration in the vehicle group brain, but no tissue lesions were observed in the vaccination group. TNF-α, IL-6, and synuclein were up-regulated in the brain of the vehicle group, while those were inhibited in the vaccination group. IFN-β, IFN-γ, ISG15, Mx1, and OAS1 showed no difference between vaccination and vehicle group in the brain. In addition, TNF-α and IL-6 were inhibited, and antiviral factors were increased in the intestine of the vaccination group compared to the vehicle group. Our study showed that PRV XJ delgE/gI/TK inhibited neurological damage and the inflammation of the intestine and brain induced by PRV and activated the innate immune of the intestine.